The Importance and Characteristics of Family Governance for Firm Performance and Competitive Advantage: A Short Literature Review - Savvina I. PAGANOU; Ioannis ANTONIADIS; Christos KONSTANTINIDIS (Communications of International Proceedings, 2023)
The importance of corporate governance is growing due to globalization and the current changes in the business environment caused by the Covid 19 pandemic. The application of good corporate governance practices can prepare small businesses for future development. The purpose of this paper is to present a short literature review on the concept of family governance and the value it provides in family businesses, by highlighting its most important aspects, and mechanisms, identifying the elements of corporate governance that contribute to performance and competitive advantage. Our study suggests that the interaction between family administration properties can produce significant adaptability and competitive advantages, especially when the CEO is not a family member and reduced corporate performance is found when control is in the hands of the next generation. Furthermore, the extent of family control and role of family CEO can significantly reduce the contribution of independent directors. Finally, we highlight topics that should be researched in the future to achieve family business sustainability.
Keywords: Family Governance; Family CEO; Independent Directors; Firm Performance